Trophoblast organoids as a model for maternal–fetal interactions during human placentation - Turco, Margherita Y.; Gardner, Lucy; Kay, Richard G.; Hamilton, Russell S.; Prater, Malwina; Hollinshead, Michael S.; McWhinnie, Alasdair; Esposito, Laura; Fernando, Ridma; Skelton, Helen; Reimann, Frank; Gribble, Fiona M.; et al. (Nature (London), 2018)
The placenta is the extraembryonic organ that supports the fetus during intrauterine life. Although placental dysfunction results in major disorders of pregnancy with immediate and lifelong consequences for the mother and child, our knowledge of the human placenta is limited owing to a lack of functional experimental models 1 . After implantation, the trophectoderm of the blastocyst rapidly proliferates and generates the trophoblast, the unique cell type of the placenta. In vivo, proliferative villous cytotrophoblast cells differentiate into two main sub-populations: syncytiotrophoblast, the multinucleated epithelium of the villi responsible for nutrient exchange and hormone production, and extravillous trophoblast cells, which anchor the placenta to the maternal decidua and transform the maternal spiral arteries 2 . Here we describe the generation of long-term, genetically stable organoid cultures of trophoblast that can differentiate into both syncytiotrophoblast and extravillous trophoblast. We used human leukocyte antigen (HLA) typing to confirm that the organoids were derived from the fetus, and verified their identities against four trophoblast-specific criteria 3 . The cultures organize into villous-like structures, and we detected the secretion of placental-specific peptides and hormones, including human chorionic gonadotropin (hCG), growth differentiation factor 15 (GDF15) and pregnancy-specific glycoprotein (PSG) by mass spectrometry. The organoids also differentiate into HLA-G + extravillous trophoblast cells, which vigorously invade in three-dimensional cultures. Analysis of the methylome reveals that the organoids closely resemble normal first trimester placentas. This organoid model will be transformative for studying human placental development and for investigating trophoblast interactions with the local and systemic maternal environment. An in vitro system that generates three-dimensional cultures of extraembryonic fetal trophoblast cells that differentiate into the two main types of trophoblast can be used to study human placental development.